A Norwegian traveller in Tibet: Theo Sörensen and the Tibetan collection at the Oslo University Library - Kværne, Per, 1945- (Bibliotheca Himalayica, 1973)
On the life of Theodor August Christian Sōrensen, 1873-1959, and his account of Tibet, 1909-1922; includes a catalog of Theo Sörensen collection of Tibetan MSS. and xylographs in the Oslo University Library.